Web Based Online Exam Application for Junior High School - David Eka Ramadhan; Ika Ratna Indra Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
Exam is one form of evaluation used to assess the delivery of lessons that have been taught by teachers to students. The test is conducted to measure the achievement of students as students. If the results of the evaluation of the student learning process are deemed not optimal, the teaching and learning process must be improved in terms of both quality and quantity. Conventional exams are currently considered less effective, because they require a large amount of money and take a relatively long time to correct test results. The purpose of this study is to facilitate students and teachers in the process of administering the exam and can increase the effectiveness of the exam. The method used in this research is the waterfall method. While the data collection technique using quantitative techniques. The result of this research is a web-based online exam application which is expected to make it easier for students to work on exam questions anywhere using available devices